Analisis Dan Perbaikan Penyebab Cacat Produk Bearing Menggunakan Metode PCA (Principal Component Analysis) Di PT NSBM Indonesia - Ilham Firmansyah; Ahcmad Fauzan; Erwin Barita Maniur Tambunan (JOURNAL SAINS STUDENT RESEARCH, 2026)
This study aims to identify the dominant factors causing bearing product defects and evaluate the effectiveness of corrective actions on Line F2 at PT. NSBM Indonesia. The study uses a comparative case study approach utilizing production data from March to August 2025, which includes production volume, defect types (shield dented and seal scratch), process parameters, and machine maintenance data. The analysis was conducted using Principal Component Analysis (PCA) to reduce the variables causing defects. The PCA results showed two main components with a cumulative variance contribution of 66.34%, where PC1 (40.13%) was influenced by machine condition, process parameters, and work methods, while PC2 (26.21%) was influenced by operator and work environment factors. Based on these results, corrective actions were focused on improving machine conditions, standardizing process parameters, and strengthening work methods and maintenance. Evaluation after countermeasure implementation showed a 100% reduction in defect rates, achieving zero defects. The results of this study prove that the combination of the PCA method and countermeasures is effective in improving the quality and control of the bearing production process in a sustainable manner.